PROBLEMS OF GENRE AND FEATURE OF GENRE SYSTEM OF CONTEMPORARY UKRAINIAN PROSE FOR CHILDREN AND YOUTH - Качак, Т. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with theoretical aspects of the formation of the genre system of contemporary Ukrainian prose for children. The author defines the main aspects that unite all the genres in the system. This is the presence of fairy-tale, game, adventure, fantastic elements as content and formal qualities of the work, genre-valued components. Within the framework of the formation "contemporary prose for children and youth", focusing on the way of representing artistic reality, distinguishes three main groups: realistic prose, realistic fantasy prose, fantastic prose. The groups comprise classical genres, synthetic genres, and modified genre forms, represented by specific works. The scheme-model of the genre system of contemporary Ukrainian prose for children and youth testifies to the tendency of genre diversity, the branching of the system of genres by updating classical genres, their transformation and complication by synthesis of heterogeneous genre elements; a combination of traditions and innovation, a manifestation of author's style.